Flexible capacitive and piezoresistive pressure sensors based on screen-printed parylene C/polyurethane composites in low-pressure range - Kurnaz, Sedat; Ozturk, Ozgür; Mehmet, Ali Hazar; Guduloglu, Utku; Yilmaz, Nurdane; Cicek, Osman (IOP Publishing, 2023)
Abstract The use of polymers to fabricate flexible pressure sensors as an alternative to conventional pressure sensors has led to the development of physiological monitoring of human body and the electronic skin. In particular, the fabrication of flexible capacitive and piezoresistive sensors using a variety of materials and the investigation of their electromechanical properties are further developments in these fields. Herein, parylene C is synthesized via chemical vapor deposition method. Pressure-sensitive inks are prepared with a composite of parylene C, polyurethane, polymethylmethacrylate, and activated carbon at certain weight ratios. Flexible capacitive and piezoresistive pressure sensors are fabricated by the screen printing method. The sensitivity, detection limit, linearity range, and response/relaxation time, which define the capacitive and piezoresistive properties are investigated and presented in this paper. The sensitivities of the flexible capacitive and piezoresistive pressure sensors are 0.124 kPa−1 and 0.074 kPa−1 in the pressure range of 0.07–1.39 kPa. This study enables parylene C to be used in the composite structure and shows that it can be used not only as a protective layer but also in flexible pressure sensor applications. It also ensures that the design of the flexible capacitance pressure sensor can measure low pressure with high sensitivity compared to the flexible piezoresistive pressure sensor.